2022
DOI: 10.3390/buildings12050667
|View full text |Cite
|
Sign up to set email alerts
|

Vision-Based Methods for Relative Sag Measurement of Suspension Bridge Cables

Abstract: Main cables, comprising a number of wire strands, constitute a vital element in long-span suspension bridges. The determination of their alignment during construction is of great importance, and relative sag is commonly measured for the efficient sag adjustment of general strands. The conventional approach uses the caterpillar method, which is inconvenient, difficult-to-implement, and potentially dangerous. In order to realize the high-precision measurement of cable alignment in a strong wind environment, a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The control of a main beam's alignment is a gradual process that may significantly affect subsequent stages. During bridge construction, experts have started carefully considering whether a girder's alignment matches that designed for adjustments [16][17][18]. Zhang et al [10] accurately identified deflections during construction and derived the relationship regarding strain for evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…The control of a main beam's alignment is a gradual process that may significantly affect subsequent stages. During bridge construction, experts have started carefully considering whether a girder's alignment matches that designed for adjustments [16][17][18]. Zhang et al [10] accurately identified deflections during construction and derived the relationship regarding strain for evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [22] proposed a vision-based method to accurately measure the cable alignment of long-span suspension bridges in a strong wind environment. Aided with pre-installed optical targets, the relative sag of cable strands was monitored remotely, automatically and in a real-time manner.…”
mentioning
confidence: 99%